2018
DOI: 10.1016/j.idm.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mobility among high-risk populations on HIV transmission in Western Kenya

Abstract: Western Kenya suffers a highly endemic and also very heterogeneous epidemic of human immunodeficiency virus (HIV). Although female sex workers (FSW) and their male clients are known to be at high risk for HIV, HIV prevalence across regions in Western Kenya is not strongly correlated with the fraction of women engaged in commercial sex. An agent-based network model of HIV transmission, geographically stratified at the county level, was fit to the HIV epidemic, scale-up of interventions, and populations of FSW i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Another limitation stems from the fact that in South Africa, the HIV epidemic is highly heterogeneous between provinces, mostly differing in prevalence of male circumcision and non-marital relationships (Johnson et al 2017a). In this context, national-level models (such as the present study) must be utilized with caution; e.g., it has been shown that spatial heterogeneity and associated migration strongly influence HIV transmission (Bershteyn et al 2018; Dobra et al 2017; Coffee et al 2007; Voeten et al 2009) and therefore vaccination implementation. Considering constrained vaccine coverage regarding heterogeneously distributed geospatial and behavioral risk would raise ethical questions of how to devise vaccine rollout in an optimal way (Keeling and Shattock 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Another limitation stems from the fact that in South Africa, the HIV epidemic is highly heterogeneous between provinces, mostly differing in prevalence of male circumcision and non-marital relationships (Johnson et al 2017a). In this context, national-level models (such as the present study) must be utilized with caution; e.g., it has been shown that spatial heterogeneity and associated migration strongly influence HIV transmission (Bershteyn et al 2018; Dobra et al 2017; Coffee et al 2007; Voeten et al 2009) and therefore vaccination implementation. Considering constrained vaccine coverage regarding heterogeneously distributed geospatial and behavioral risk would raise ethical questions of how to devise vaccine rollout in an optimal way (Keeling and Shattock 2012).…”
Section: Discussionmentioning
confidence: 96%
“…[116,117]), and IBMs are being used more frequently to understand disease epidemiology (e.g. [118,119]).…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of 14 ESA priority countries, Kripke et al found that costs per infection averted ranged from US$1300 to $22,000 [ 65 ••]. The variability was driven more by the wide differences in HIV incidence across ESA settings [ 13 , 81 – 83 ] (Fig. 1 a) than by differences in unit costs of VMMC (Fig.…”
Section: Cost and Cost-effectiveness Of Vmmcmentioning
confidence: 99%